2017
DOI: 10.3892/ijmm.2017.3138
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of HIF1A-AS1 and HIF1A-AS2 in regulating HIF-1α and the osteogenic differentiation of PDLCs under hypoxia

Abstract: Hypoxia‑inducible factor‑1α (HIF‑1α) is essential for regulating the osteogenic differentiation of periodontal ligament cells (PDLCs). The regulatory mechanism of HIF‑1α transcription is still not clear. Recently, two long non‑coding RNAs, HIF1A antisense RNA 1 (HIF1A‑AS1) and HIF1A antisense RNA 2 (HIF1A‑AS2), were found to regulate HIF‑1α mRNA, but the regulatory mechanisms among HIF‑1α, HIF1A‑AS1 and HIF1A‑AS2 have not been well studied. We hypothesized that HIF1A‑AS1 and HIF1A‑AS2 play important roles in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 35 publications
3
38
0
Order By: Relevance
“…P-value = 5e-6) but not its own promoter or that of HIF1A-AS1 while both regions had consensus HIF binding sites and active chromatin marks ( Figure S7). Combined with our expression profiles, these observations suggest a feedback regulatory role for HIF1A-AS2 and/or EPAS1 in HIF1A expression as seen in periodontal ligament cells ( (38) and renal cell carcinoma and glioblastoma cells (39).…”
Section: Temporal Activation Of the Hypoxic Programsupporting
confidence: 69%
“…P-value = 5e-6) but not its own promoter or that of HIF1A-AS1 while both regions had consensus HIF binding sites and active chromatin marks ( Figure S7). Combined with our expression profiles, these observations suggest a feedback regulatory role for HIF1A-AS2 and/or EPAS1 in HIF1A expression as seen in periodontal ligament cells ( (38) and renal cell carcinoma and glioblastoma cells (39).…”
Section: Temporal Activation Of the Hypoxic Programsupporting
confidence: 69%
“…HIF1A-AS2 has already been found upregulated in some cancers; its influence on maintenance of mesenchymal glioblastoma stem-like cells is noteworthy [11]. Chen et al revealed that HIF1A-AS1 and HIF1A-AS2 took part in periodontal ligament cell (PDLC) osteogenic differentiation which was regulated by hypoxia-inducible factor-1α (HIF-1α) [15]. It was primarily proved that HIF1A-AS1 played a role in PDLC osteogenic differentiation and it still needed further research in ASCs.…”
Section: Discussionmentioning
confidence: 99%
“…HIF1A-AS2 is a kind of lncRNA which facilitates several cancers, such as colorectal cancer, bladder cancer, and glioblastoma [1012]; it is considered as a diagnostic biomarker of the development in differentiation between diverse breast cancer types [13], as well as an influence on other processes including HUVEC angiogenesis [14]. A recent study revealed that HIF1A-AS1 and HIF1A-AS2 played a role in regulating hypoxia-inducible factor-1α (HIF-1α) and further affected periodontal ligament cell (PDLC) osteogenic differentiation [15]. But the effect of HIF1A-AS2 on ASC osteogenic differentiation still needs more exploration.…”
Section: Introductionmentioning
confidence: 99%
“…HIF1A-AS3 is one of the three antisense genes of HIF1A. Another antisense, HIF1A-AS2, is involved in the regulation of HIF-1ɑ [12,43]. HIF1A-AS2 mRNA was not significantly higher in the CP of progressive MS patients relative to that of controls, suggesting that HIF1A-AS3 may act as an upstream regulator of the hypoxia responses observed in our study.…”
Section: Discussionmentioning
confidence: 44%